A Study on Distribution Channels in Corporate Hospitals - Sreenivas, Dr. T.; Rao, Dr.U.Srinivasa (SMART MOVES JOURNAL IJELLH, 2017)
Place is one of the key element for effective distribution of hospital services. It means the hospital should be easily accessible to the patients, at the same time should be adequately protected from pollution. The objective of the study is to investigate and compare the place mix (distribution) in selected super-specialty hospitals and making suitable suggestions on the basis of statistical analysis of perceptions collected from Doctors, Nurses and Administrative Personnel on place mix of sample hospitals. The collected data is analyzed by applying descriptive and inferential statistical techniques such as mean, standard deviation. It is concluded that the perceptions of respondents on place mix are positively opinioned in two sample hospitals. The Grand Mean and S.D. scores are in the range of 2.55 to 2.79 (Grand Mean) 0.38 to 0.48 (S.D) in APOLLO and 2.52 to 3.01 (Grand Mean) 0.32 to 0.36 (S.D) in CARE respectively, on a 5 point scale indicating place mix of the sample hospitals is agreeable to the respondents.